Epidemiologia e controle da mancha aureolada do cafeeiro - Freitas, Marcelo Loran de Oliveira (2017)
In recent years, the Pseudomonas syringae pv. Garcae (Psg) has caused damage to the coffee plantations located in several regions. From its epidemiology to its control, studies are still needed. The objectives were to evaluate the efficiency of different molecules of the cupric chemical group in the management of the bacterial blight of coffee and its phytotoxic potential in coffee tree seedlings; To evaluate the in vitro multiplication of the bacterium at different temperatures and the interaction of the temperature with the duration of leaf wetness on the severity of the bacterial blight of coffee seedlings inoculated with and without injury and to study the temporal distribution of bacterial blight of coffee, attribuites and soil fertility, altitude, coffee production, enfollowing, and nutrition of coffee using geostatistics, as well as to analyze the correlation of the disease with climatic variables. According to the results, cuprous oxide and copper sulphate (Bordeaux mixture) at 2500 mg.kg -1 were the most efficient in the control of bacterial blight of coffee, causing less toxicity and providing greater leaf tissue coverage of seedlings of coffee. In vitro assay the highest population growth of Psg occurred in the interval between 23 and 31 ° C, with a peak at 28.1 ° C. In the in vivo assay the wound inoculation provided higher AACPS of the bacterial blight of coffee in relation to the inoculation without injury. In the plants inoculated by injury, the variation of leaf wetness duration had little influence on AACPS. The maximum AACPS was achieved at temperatures of 20.9 and 19.3 ° C and leaf wetness durations of 48 and 35.5 hours when inoculated with and without injury, respectively. The bacterial blight of coffee showed spatial distribution and appeared in a single large focus on the area located on the south face of the land in the two years reducing the production of the affected plants. The highest levels of the disease were in the places with the highest levels of phosphorus in the foliar tissue of the coffee and higher altitude, being in the highest altitudes, the highest wind speed, and the lowest average air temperature. While the lowest levels of the disease in the sites with the highest Cu present in the leaf.